The Feminine Other: Monsters and Magic in Beowulf and Sir Gawain and the Green Knight - Hana Ghani (J-Lalite: Journal of English Studies, 2021)
Monsters are perceived as humanity’s enemy that should be eradicated. However, based on Jeffrey Cohen’s Monster Theory (1997), monsters play an important role in understanding humanity’s fears and anxieties. Monstrosity hinges upon the binary opposition of the Self and the Other, in which the Other is seen as a threat to the Self. With this in mind, this article addresses the female monsters of two medieval texts: Beowulf and Sir Gawain and The Green Knight. This paper aims to examine the female monsters, Grendel’s mother and Morgan the Fay, as a cultural reference to unravel the patriarchal anxieties of the time. Grendel’s mother represents a threat to the homosocial hierarchal bonds of Medieval society. Meanwhile, Morgan the Fay signifies danger to knighthood, chivalry, and courtly romance. At the same time, this paper also aims to continue the critical analysis and literature of the female characters in both texts with a heavy emphasis on their Otherness.